Bilingual linguographic sources: parametric analysis - Guzel N. Karimullina, Rezeda N. Karimullina, (Opción, 2019)
The article gives a parametric analysis of linguistic reference books, which provides information about what data are contained and how they are presented in bilingual and monolingual dictionaries of the Russian-Tatar of the second half and beginning of the 20th and the 21st centuries via the linguistic description, comparative and contrastive methods. For the character of representation, a parameter can be principal and not main. By the representation character, a parameter may be principal and non-principal. The parametric analysis is reflected in a summary table, where lines show parameters and columns  abbreviated titles of dictionaries.